Online and Offline Service Quality Assistance at Ratu Hijab Online Shop - Robustin, Tri Palupi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This online shop business has several guarantees as a beginner online business venture, first because online consumers need original images or original images of clothes, veils, mukena so they need several statues. In addition, the second problem is in providing quality offline service to consumers when wrapping goods that are still very simple, so this reflection team provides a solution in terms of wrapping goods by making stickers that contain complete information related to Ratu Hijab, so that the items sent look neat and the information is clear. . This community service activity aims to provide assistance to Ratu Hijab online shop owners regarding the quality of online and offline services. The assistance is in the form of providing solutions and innovations related to marketing strategies so that consumers get good service related to sales promotions by displaying real images during promotions. In addition, the service team also provides solutions related to wrapping goods to be sent to consumers by providing labels / stickers related to the queen's hijab information, such as address, cellphone number and various items sold.